CHARACTERISTICS OF STUDENTS' SCIENTIFIC AND CREATIVE ACTIVITIES (British Journal of Global Ecology and Sustainable Development, 2023)
In the article, scientific creativity is considered as the main process in students' activities, and theoretical and experimental information about the role of participation in scientific works and in the creative thinking of students was presented.